H. Binga Dismond, MD--pioneer Harlem physician and much more. - Oestreich, A. E. (National Medical Association, 2001)
All physicians hopefully have some interests beyond their specialty. Dismond exemplified a broad range of activities, including athletics, military service, poetry, multiple marriages, and socializing, as well as two specialties in medicine.